Project based learning via open ended projects: Approach of comprehensive learning and skills development in civil engineering laboratory / Asmidar Alias ... [et al.] - Alias, Asmidar; Mohd Nor, Nur Asmaliza; Mohd Latib, Farah Wahida; Mohamad Bhkari, Norshariza (2012)
The approach in Outcome-Based Education (OBE) in a way promotes educators to be more comprehensive in, all aspect in teaching and learning. This trend is to create a balance between technical and non-technical aspects in the training and education of engineers. The shift has been shown .in engineering education and curricula design worldwide. The new curricular has been designed in such way students be able to grasp the cognitive part in their learning as well as acquired skills needed in engineering industry. The challenges are to establish effective teaching and well-designed assessment to develop highly competent technical persons as well as social skills. It is ideally to nurture students' skill in analytical, logical, organized and structured thinking stems. However, all engineering schools in Malaysia have adapted OBE of the new higher learning education thus need to enhance people skills in conceptual and holistic thinking. The literature section will cover all aspects that concern OBE, co-operative learning, project based learning and assessment. This paper examines the effectiveness of well- design assessment and students' perception for open ended project. Using cluster sampling. students are selected from semester 4 and analyzed based on given questionnaire. The data shows students agree that there is significant course outcomes achievement by using open ended project and incorporated with conceive - design - implement - operate (CDIO) method.